ASSESSMENT OF ALIZARIN, PURPURIN AND GENETIC FIDELITY OF RUBIA CORDIFOLIA L. FROM EASTERN GHATS OF TAMIL NADU, INDIA - NATARAJAN SISUBALAN,; AMZAD BASHA KOLAR,; MOHAMED HUSSAIN GHOUSE BASHA, (International Journal of Pharma and Bio Sciences, 2015)
Rubia cordifolia L. is a widely used medicinal plant belongs to the family Rubiaceae. The evaluation of the alizarin, purpurin and genetic fidelity of Rubia cordifolia L. is crucial for the identification of this economically and ecologically valuable climber. In this study, we quantify the phytochemicals (alizarin and purpurin) using RP-HPLC analysis and Genetic fidelity studies carried out using RAPD markers. Phytochemical studies showed gradual variation among the samples. The maximum amount of alizarin and purpurin was found in the plant samples of Kalrayan hills (GBR3- 32.4% and 33.4%) followed by Kolli Hills (GBR1- 27.0% and 16.5%), Pachamalai (GBR6- 23.8% and 20.7%), Shervaroy hills (GBR2 16.6% and 9.4%), Jawadhu hills (GBR5- 13.4% and 11.7%), Chitteri hills (GBR4- 12.9% and 0.59%) and Yelagiri hills (GBR7 8.7% and 0.87%) respectively. 15 RAPD primers were used to distinguish the genetic fidelity among Rubia cordifolia L. collected from Eastern Ghats of Tamil Nadu. 15 RAPD primers amplified 246 polymorphic bands. Each primer classified the species under investigation into clear, completely separated clusters, although maximum conformity was achieved with respect to species relationships when the RAPD method was employed. Overall, results indicated that RP-HPLC represents an effective tool for phytochemical studies and RAPD represents an efficient molecular marker system for the assessment of genetic fidelity and diversity.